A case report on acute combined poisoning of Indoxacarb and Novoluron and its management - Rohita Chitithoti; Chopparapu Sai Supraja; Danaboyina Sreelekha; Sri Lakshmi Sai Meghana Adusumilli; Ramireddy Veerareddy; Puppala Santosh (SAGE Open Medical Case Reports)
In India, it is not uncommon for individuals to attempt suicide by ingesting pesticides. Though several publications have reported cases, there are no specific guidelines for managing indoxacarb poisoning. There is no established antidote for indoxacarb poisoning; however, early recognition and treatment of methemoglobinaemia, the primary manifestation, is essential. Early intervention is crucial for a positive outcome. Methemoglobinaemia can be successfully treated with methylene blue, which serves as the first line of management. This case report describes a 24-year-old man presenting with methemoglobinaemia following the ingestion of indoxacarb combined with novaluron and was successfully treated with early administration of methylene blue, leading to rapid recovery despite a methaemoglobin level as high as 75%.